2008
DOI: 10.1021/jo8013897
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of Difficult Peptide Sequences at Elevated Temperatures: A Critical Comparison of Microwave and Conventional Heating Technologies

Abstract: The Fmoc/t-Bu solid-phase synthesis of three difficult peptide sequences (a 9-mer, 15-mer, and 24-mer) was performed using N,N'-diisopropylcarbodiimide/1-hydroxybenzotriazole as coupling reagent on polystyrene, Tentagel, and ChemMatrix resins. In order to obtain an insight into the specific role of the elevated temperature and/or the electromagnetic field for peptide syntheses carried out using microwave irradiation, peptide couplings and Fmoc-deprotection steps were studied under microwave and conventionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
0
10

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(150 citation statements)
references
References 112 publications
6
129
0
10
Order By: Relevance
“…This is supported by the observation that no such difficulties were encountered in the synthesis of either UBI30-41 or its NOTA-conjugate, both lacking the threonine residue at the amino terminal. The most common reason for persistent difficulty in synthesizing a peptide using microwave-assisted solid phase synthesis are unfavorable intramolecular and/or intermolecular interactions of the nascent peptides, which may result in secondary structure conformations which inhibit coupling of additional amino acids [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the observation that no such difficulties were encountered in the synthesis of either UBI30-41 or its NOTA-conjugate, both lacking the threonine residue at the amino terminal. The most common reason for persistent difficulty in synthesizing a peptide using microwave-assisted solid phase synthesis are unfavorable intramolecular and/or intermolecular interactions of the nascent peptides, which may result in secondary structure conformations which inhibit coupling of additional amino acids [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…However, if there is no idea about exact internal reaction temperature, this type of reactions cannot be carried out or they may give incorrect outputs (Herrero, Kremsner, & Kappe, 2008;Bacsa et al, 2008). A single-mode high field-density microwave reactor (2.45 GHz, 850 W) along with internal fiber-optic temperature control had been used in the reactions to monitor the reaction temperature accurately in a small scale(0.5-2 mL) (Obermayer, Gutmann, & Kappe, 2009;Gutmann et al, 2010).…”
Section: Applications In Proteomicsmentioning
confidence: 99%
“…They have also used microwave instrumentation that has no internal probe to monitor the actual reaction temperature directly. Instead, they have used external IR sensors to monitor the surface temperature of the reaction vessel (Herrero, Kremsner, & Kappe, 2008;Bacsa et al, 2008) reported unreliability of these sensors with highly viscous reaction mixtures.…”
Section: Applications In Proteomicsmentioning
confidence: 99%
“…microwave (MW) irradiation has become a preferred choice for the organic chemist [1,[14][15][16]. There are many examples of the application of MW irradiation in peptide synthesis, including automated peptide synthesizers equipped with MW capability [17][18][19][20][21][22]. The main advantages of MW-assisted chemistry are shorter reaction times and higher yields.…”
Section: Introductionmentioning
confidence: 99%